Dual-Wavelength Erbium-Doped Fiber Laser to Generate Terahertz Radiation Using Photonic Crystal Fiber - Soltanian, Mohammad Reza K.; Amiri, Iraj Sadegh; Alavi, S. Ehsan; Ahmad, Harith (Institute of Electrical and Electronics Engineers, 2015)
We demonstrate a widely tunable dual-wavelength erbium-doped fiber laser that used a 10-cm photonic crystal fiber as a Mach-Zehnder interferometer to filter out the switchable dual-wavelength signals so as to generate tunable continuous-wave (CW) terahertz (THz) radiation. Each single longitudinal mode wavelength could be independently tuned by using a tunable band-pass filter and polarization controller (PC). The wavelength fine-tuning was achieved via adjustments to the PC, and the resulting dual-wavelength output had a side-mode suppression ratio (SMSR) of more than 30 dB. The wavelength spacing of 7, 11.4, and 21.2 nm, corresponding to 0.9, 1.4, and 2.66 THz radiation, respectively, was tuned in order to obtain CW THz radiation. This CW THz radiation was produced by means of a stable dual-wavelength fiber laser performing as the optical beat source, together with a DAST crystal-based photomixer. High-sensitivity thermal sensors calibrated for THz radiation were able to continuously detect the emitted CW THz radiation.